A Chandra survey of the SMC Bar: First Results - McDowell, J. C.; Zezas, A.; Taylor, P. A.; Hatzidimitriou, D.; Kalogera, V.; Fabbiano, G. (2003)
We summarize the early results from a Chandra X-ray Observatory survey of the central region of the Small Magellanic Cloud, dominated by a recent burst of star formation. We detect 122 sources in five ACIS fields, reaching a 0.1-10 keV luminosity (corrected for Milky Way absorption ) of 4.3× 1033 erg/s, an order of magnitude deeper than previous surveys. Our survey includes 20 candidate transient sources and measures extent in 5 supernova remnants. The data indicate fewer very faint sources than would be expected from the background. We compare our results with ROSAT and ASCA observations of the region; many of the ASCA sources are found to suffer from confusion. We are beginning a program of optical identifications for the newly discovered sources. The companion poster by Taylor et al. describes our X-ray spectral and timing analysis on the bright sources. We acknowledge support from the Chandra X-ray Center (NASA contract NAS8-39073).